The immediate effects of serving on shoulder rotational range of motion in tennis players. (November 2018) - Williams, Katy; Hebron, Clair
Abstract: Objective: This study aimed to investigate the immediate effects of serving on shoulder rotational range of motion (ROM) in tennis players by comparing to groundstrokes. Design: Same-subject, randomised, crossover study. Setting: Indoor hard courts. Participants: Eighteen male and 12 female professional and university level tennis players. Main outcome measures: Passive glenohumeral internal and external rotation ROM measurements, using a digital inclinometer, were undertaken at baseline and immediately following serving and groundstroke tasks on both dominant and non-dominant shoulders. Total rotation was calculated as the sum of internal and external rotation. Results: On the dominant and non-dominant shoulders there was no significant interaction effect between the factors of tennis task (serving and groundstrokes) and time (pre and post) ( p = <0.05). Indicating that change in rotational ROM was not specific to tennis task. On the dominant shoulder there was a significant main effect of time (p = 0.007), with internal, external and total rotational ROM decreasing irrespective of tennis task. Conclusion: Both tennis tasks resulted in immediate significant reductions in shoulder rotational ROM on the dominant shoulder but not the non-dominant shoulder of professional and university tennis players. There was no significant difference between serving and groundstroke tasks. Highlights: Exposure to different tennis strokes resulted in immediate significant reductions in shoulder rotational ROM. This occurred on the dominant shoulder but not the non-dominant shoulder of tennis players. ROM reductions were within normal ranges that do not present risk factors for shoulder injuries in overhead athletes. Comparing serving to groundstrokes, there were no significant differences between the strokes on shoulder rotational ROM.